Gasification of Dry Biomass with Carbon Dioxide Sequestration - Kumar, Hemant (My University, 2017)
Gasification, a thermo-chemical process, is explored as a promising technology towards carbon capture. The present work focuses on using CO2, from the product of combustion of fuels in an engine or a combustion device, as a co-reactant along with other reacting media. Experiments were conducted with CO2 volume fraction varied from 0 to 15% in a mixture of O2 and N2. Increase in CO2 fraction resulted in decrease in bed temperature, primarily due to reduction in O2 fraction, in the gasifying medium, and the endothermic reaction of char and CO2. Low bed temperature was addressed by maintaining the O2 volume fraction in the input at 21% by introducing additional oxygen. At 15% CO2 injection, the CO fraction increased from 13.1% to 16.3% and over 55% of the input CO2 conversion was noted. Recorded an increase in cold gas efficiency by 30% owing to higher conversion rate of char. Working with the engine exhaust also eliminates the cost incurred in separation of CO2 and makes the system less complicated. Further, thermodynamic equilibrium studies has been performed addressing the issue of lower bed temperature during experiments. with CO2 as reactant. NASA SP 273 software has been employed to study the temperature variation under adiabatic and isothermal condition. Equilibrium analysis has provided an oppurtunity to identify the optimum O2 fraction required to maintain the bed temperature with CO2 as reactant similar to those of air gasification. The higher O2 fraction with increased CO2 in input has been identified and analysed. The system is found to shift from gasification to combustion regime with the increase in Euivalence Ratio (ER) as O2 fraction increases with CO2 fraction. The operation at higher ER is leading to slightly lower efiiciencies. Present work recommends to operate at O2 fraction of 21% when CO2 fraction in reacting media is low but to operate at higher O2 at higher CO2 fractions. The experiments at higher O2 fractions is suggested as future work.
ME Dissertation
Keywords: Biomass; Sequestration; CO2 Reduction; CO2 Capture